The Significance of Pancasila Education in Higher Education Institutions for Improving Students’ Legal Awareness - Roberto Sitepu; Etty Indrawati; Richard Willie Handoyo (West Science Law and Human Rights, 2026)
Pancasila is the philosophical foundation of the Indonesian nation, serving as the guiding vision for education and character development. One aspect of character building that is important to develop through Pancasila Education is the development of legal awareness, especially in shaping students who understand their own rights and obligations and those of others, and in creating an orderly and fair environment. This study aims to analyze the significance of Pancasila Education in increasing legal awareness among university students and to identify strategies for implementing Pancasila Education in order to increase legal awareness among university students. This study employs a combination of qualitative and quantitative methods, utilizing a normative approach. The results of the study show that Pancasila Education is still significant in higher education to increase legal awareness among students, with adaptive implementation and strong dedication needed to overcome challenges and maintain its relevance among students.